Analysis of molecular resistance to azole and echinocandin in Candida species in patients with vulvovaginal candidiasis - Ensieh Lotfali; Mahzad Erami; Mahsa Fattahi; Houshang Nemati; Zeinab Ghasemi; Elham Mahdavi (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Vulvovaginal candidiasis (VVC) is considered the most common mucosal infection caused by Candida species. Azoles were considered the firstline treatment for VVC or recurrent vulvovaginal candidiasis (RVVC) in both healthy and immunocompromised populations. Recently, azole-resistant isolates, especially among non-albicans Candida samples have been encountered. This study aimed to evaluate the antifungal susceptibility profile of Candida spp. isolated from VVC or RVVC patients and assess the molecular resistance mechanism of Candida spp. to azole and echinocandin.Materials and Methods: Point mutation analysis was performed on the ERG11 and FKS candidate genes of azole- and caspofungin-resistant Candida albicans and Candida glabrata isolates. Real-time polymerase chain reaction was performed to gain insight into the differential expression of ERG11 mRNA.Results: Variations in the amino acid D116E were observed in fluconazole- and itraconazole-resistant C. albicans strains, and changes in amino acid E517Q were observed only in fluconazole-resistant C. albicans strains. No polymorphisms were observed in the complete sequence alignment of the ERG11 gene in one azole-resistant C. glabrata isolate. The mutation triggered the changes in the amino acid serine in the reference gene FKS1 by the leucine at position 642 (S642L) of the isolates.Conclusion: In patients with persistent or recurrent infection, the choice of an antifungal agent is often challenging and requires monitoring of the antifungal susceptibility of the colonizing strain. C. albicans and C. glabrata isolates can be resistant to azole and caspofungin antifungal agents without mutations in the ERG 11 and HS1 regions of the FKS1 gene.